Border visions : identity and diaspora in film - Kazecki, Jakub; Ritzenhoff, Karen A.; Miller, Cynthia J., 1958- (The Scarecrow Press, Incorporated, 2013)
This book offers an overview of global cinema that addresses borders as spaces of hybridity and change. In this collection of essays, contributors examine how cinema portrays conceptions of borderlands informed by knowledge, politics, art, memory, and lived experience, and how these constructions contribute to a changing global community. These essays analyze a variety of international feature films and documentaries that focus on the lives, cultures, and politics of borderlands. The essays discuss the ways in which conflicts and their resolutions occur in borderlands and how.